“INDY CLASSICAL INNOVATION: YMUSIC” AT USC’S SOUTHERN EXPOSURE NEW MUSIC SERIES - Kay, Peter B. (Dialogue, 2(1), 2015)
Quiet fills the concert hall. A young man, about 30 years old, stands in front of the audience. With him are a number of musicians in what appears to be a traditional ensemble, but with a few interesting and unusual changes. The young man is stylishly dressed, his clothes a mix of fashion and formality. His hair is a bit long and a little unruly, but this is the trend for young artists and musicians. The audience, mostly made up of 20-, 30-, and 40-somethings, do not seem to notice these small departures from tradition. They are simply eager to hear what this new composer has written...
Keywords: Type of access: Open Access